2021
DOI: 10.3390/ijerph182312712
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Effects of Multi-Dimensional Urbanization on Carbon Emission Efficiency: Analysis Based on Panel Data of 283 Cities in China

Abstract: Under the influence of complex urbanization, improving the carbon emission efficiency (CEE) plays an important role in the construction of low-carbon cities in China. Based on the panel data of 283 prefectural-level cities in China from 2005 to 2017, this study evaluated the CEE by the US-SBM model, and explored the spatial agglomeration evolution characteristics of CEE from static and dynamic perspectives by integrating ESDA and Spatial Markov Chains. Then, the spatial heterogeneity of the impacts of multi-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…In addition, the LMDI approach provides evidence on the drivers of macrofactors such as economic activity, industrial structure [48], and energy intensity. Still, its inability to capture inputoutput mechanisms is frequently cited [49,51]. Nevertheless, these empirical findings are complementary, and together they warn policymakers of the importance of sustainable growth by improving factor structure and upgrading technology.…”
Section: Discussion Of Empirical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the LMDI approach provides evidence on the drivers of macrofactors such as economic activity, industrial structure [48], and energy intensity. Still, its inability to capture inputoutput mechanisms is frequently cited [49,51]. Nevertheless, these empirical findings are complementary, and together they warn policymakers of the importance of sustainable growth by improving factor structure and upgrading technology.…”
Section: Discussion Of Empirical Resultsmentioning
confidence: 99%
“…In recent years, nonparametric methods based on DEA have also been more widely used in environmental efficiency evaluation. Carbon emissions are considered input factors [15] or undesired outputs [50] in DEA models, and the optimal solution of the model is usually used to measure carbon efficiency [51]. Based on the multiperiod efficiency indices of different production technology DEA models, total factor productivity (TFP) can also be calculated by constructing productivity indices.…”
Section: Drivers Of Carbon Productivitymentioning
confidence: 99%
“…This paper constructs a comprehensive city size index ( ) from the urban population (pop) and the urban built-up area (area) indicators. Because a single indicator cannot accurately measure the city size, we constructed a comprehensive city size indicator from the perspective of urban population and built-up area based on Zhou’s work [ 40 ]. Weight refers to the importance of a factor or indicator relative to something.…”
Section: Research Methods and Data Sourcesmentioning
confidence: 99%
“…Weight refers to the importance of a factor or indicator relative to something. Many studies have shown that the weights of all factors or indicators add up to 1 [ 40 , 41 ]. Because the urban population affects the travel flow, the urban built-up area affects the travel scope, and the travel cost is affected by the urban built-up area and the population.…”
Section: Research Methods and Data Sourcesmentioning
confidence: 99%
“…The urbanization rate of China has increased dramatically over the last four decades, from 17.9% in 1978 to 60.6% in 2019 [5], and the urban population of the country is expected to surpass 75% of the overall population by 2050 [6]. Urbanization is accompanied by industrial economic growth, increasing energy consumption, lifestyle changes, and changes in land use types due to economic and social progress, all of which have a significant influence on carbon emissions [7]. The Chinese government urged China at the 75th United Nations General Assembly in September 2020 to increase its efforts to reduce emissions on its own and strive to achieve peak carbon dioxide emissions by 2030.…”
Section: Introductionmentioning
confidence: 99%